2010
DOI: 10.2176/nmc.50.977
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Revascularization Surgery for Moyamoya Syndrome Associated With Graves' Disease

Abstract: Appropriate management of moyamoya syndrome associated with Graves' disease is undetermined because of the rarity of this combination. Patients tend to present with cerebrovascular events such as transient ischemic attack (TIA) in a thyrotoxic state, which is relieved by proper antithyroid therapy. Four patients with moyamoya syndrome associated with Graves' disease were successfully treated with revascularization surgery on 5 hemispheres among 58 consecutive patients (2-62 years old, mean 34.4 years) with moy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In this study, we demonstrated that the frequency of thyroid diseases, including GD and HT, is high in HLA-DRB1*04 : 10 -positive MMD patients compared with that in HLA-DRB1*04 : 10 -negative MMD patients, suggesting the relationship between the HLA-DRB1*04 : 10 haplotype and MMD and autoimmune thyroid diseases. Many studies have reported the association between thyroid dysfunction and MMD [712], suggesting that elevated autoantibody concentrations and hyperthyroidism are associated with stenotic lesions in the terminal portion of the internal carotid artery and aggressive MMD presentations [712]. However, the underlying mechanism of this association remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that the frequency of thyroid diseases, including GD and HT, is high in HLA-DRB1*04 : 10 -positive MMD patients compared with that in HLA-DRB1*04 : 10 -negative MMD patients, suggesting the relationship between the HLA-DRB1*04 : 10 haplotype and MMD and autoimmune thyroid diseases. Many studies have reported the association between thyroid dysfunction and MMD [712], suggesting that elevated autoantibody concentrations and hyperthyroidism are associated with stenotic lesions in the terminal portion of the internal carotid artery and aggressive MMD presentations [712]. However, the underlying mechanism of this association remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…Endo et al reported the return of neurological symptoms associated with recurrent hyperthyroidism and discussed the efficacy of revascularization surgery. 16) Revascularization surgery appears acceptable for use when areas of vascular stenosis remain, despite adequate medication.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of elevated levels of thyroid antibodies detected in some patients presenting with signs of ischemia secondary to moyamoya disease, even without impaired thyroid functionality (3). Given the increased presence of T-cells within affected vessels, the possibility for T-cell-mediated cross-reactivity between TSH receptor antibodies, and antigens within the cerebral arteries, as well as impaired T-cell function may be a common pathogenetic factor in both diseases (4, 5, 6, 7). Colleran et al (8) has elicited a positive correlation between elevated thyroxine levels with increased homocysteine and methylmalonic acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral oxygen consumption also increases, whereas cerebral perfusion decreases due to elevated sympathetic tone and subsequent vasoconstriction (5, 6, 1, 7). Smooth muscle and endothelium of vasculature are influenced by excess circulating thyroid hormones such that the combination of stiffened arteries seen in GD and the significant stenosis observed in MMD predisposes affected individuals to ischemic events and may even pose greater risk than either disease alone (5, 1, 9, 10). In other words, during marked hyperthyroid states, cerebral oxygen demand increases, whereas perfusion decreases and exceeds the compensatory mechanism offered by moyamoya collateral vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation